Partisipasi Jepang Dalam Pembangunan Transportasi Moda Raya Terpadu Indonesia Melalui Forum Group of Twenty (G-20) - Suryanti, Made Selly Dwi; Prayoga, Firlantio Alen Chandra (Andalas Institute of International Studies, 2023)
As a developed country with leading expertise in the field of transportation infrastructure, Japan plays a very influential and vital role in the development of the MRT project in Indonesia. The contribution made by Japan through their expertise and experience in building transportation infrastructure can bring substantial benefits to the development of MRT in Indonesia. This research aims to explain the relations between Indonesia and Japan through the Group of 20 (G-20) meeting held in Bali in 2022. By using qualitative descriptive methods, this study will draw more on secondary data contained in related literature and online sources. The results of this research show that Japan's participation in the Group of Twenty (G-20) provides an important context for examining its role and contribution in the context of multilateral cooperation. The G20 is an international forum consisting of developed and developing countries that discusses global economic and financial issues. Within the G20 framework, Japan can interact with other member countries and increase their collaboration in developing MRT transportation in Indonesia. It is hoped that this research will contribute to adding to the literature related to bilateral cooperation, international economics in the study of international relations.